Micro-anatomical and immunohistochemical characterization of the terminal portions of the lung in the sperm whale (Physeter macrocephalus), the fin whale (Balaenoptera physalus), and the bottlenose dolphin (Tursiops truncatus) - Otero Sabio, Cristina; Centelleghe, Cinzia; Graïc, Jean-Marie; Cozzi, Bruno; Arbelo Hernández, Manuel Antonio; Fernández Rodríguez, Antonio Jesús; Peruffo, Antonella (2019)
The lungs of cetaceans underwent physiological and anatomical adaptations that facilitate extended breath-holding during the dives, including the long and deep ones. On the contrary, the time spent at the surface for gas exchange is very short. Here we present our results on the relatively unknown micro-anatomy of the terminal portions of the lungs of fin (Balaenoptera physalus) and sperm (Physeter macrocephalus) whales. For comparison we examined also the most investigated lungs of the bottlenose dolphin (Tursiops truncatus). Our study focuses on small bronchioles, cartilage rings and alveoli. For this purpose, we executed routine histological techniques, and performed both an indepth immunohistochemical (IHC) characterization, and a morphometric analysis of the terminal portions of the lung. For the IHC analyses, we employed commercial anti-human antibodies (Abs) against i) smooth muscle actin; ii) smooth muscle myosin; and iii) desmin. Results revealed that, in the bottlenose dolphin, a system of myo-elastic sphincters (MESs) is present up to the alveolar end of the terminal bronchioles. This MESs system consists of a series of sphincters placed at short intervals that constrict the lumen and divide the airways in chambers. In fin and sperm whales, smooth muscle bundles (SMB) were observed throughout the terminal bronchioles until the entrance of the alveolar sacs. However, contrarily to the MESs system, these latter structures do not constrict the lumen. Cartilage rings were present until the level of the entrance to the alveoli in the lungs of all the species. On the other hand, the alveolar size and wall thickness varied greatly. All the Abs used showed positive immunolabeling in all species sections, except for the smooth muscle myosin, which was not detectable in the sperm whale tissues. The present study provides the first IHC and quantitative morphometric analyses of the terminal portion of the lungs in selected cetacean species.